2019
DOI: 10.5005/jp-journals-10024-2502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Discoloration of Microhybrid and Nanohybrid Composite Resins by Different Beverages: A Spectrophotometric Analysis

Abstract: Background: Composite resins are choice of restorations due to their lifelike characteristics. Recently "microhybrid "and "nanohybrid" composites have been introduced. Microhybrids and Nanocomposites have a small particle size and possess better qualities as compared to traditional composite resins. The intake of beverages like black tea, coffee green tea has increased in the community. The beverages cause discoloration with time on the composite restorations making it aesthetically unacceptable.Aim: Aim is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, the third null hypothesis of this study was rejected. Previous studies have reported that coffee is the most frequently applied solution for coloring resin composites [21,[39][40][41][42]. Discoloration, which mostly occurs due to the adsorption and absorption of exogenous pigments, is an important and influential factor of the color instability of restorations [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the third null hypothesis of this study was rejected. Previous studies have reported that coffee is the most frequently applied solution for coloring resin composites [21,[39][40][41][42]. Discoloration, which mostly occurs due to the adsorption and absorption of exogenous pigments, is an important and influential factor of the color instability of restorations [35].…”
Section: Discussionmentioning
confidence: 99%
“…Resin composites are mostly used in conservative dental restorations instead of amalgam owing to their excellent cosmetic properties and ability to bond strongly to the tooth. Revision or replacement of composite restorations, which is costly and time-consuming, is commonly required because of discoloration [ 2 ]. Both the science and technology of composite dental restorative materials have advanced considerably, resulting in the development of new composite resin materials [ 3 ].…”
Section: Introductionmentioning
confidence: 99%